Handbook of research on digital therapies in psychosocial rehabilitation and mental health - Marques, Antonio Jose; Queiros, Ricardo (IGI Global, 2022)
"This book introduces the reader to the latest digital innovations in the mental health field, points out new ways in patient care and describes the limits of its application with a goal to provide an understanding of the current state of digital mental health interventions and the factors influencing the ongoing transformation of the mental health sector.
Includes bibliographical references and index
Section 1. Mobile mental health. Chapter 1. Mobile mental health: opportunities and challenges ; Chapter 2. Mobile mental health for depression assistance: research directions, obstacles, advantages, and disadvantages of implementing mhealth -- Section 2. Computer-based or web-based psychosocial interventions. Chapter 3. The road to digitally-driven mental health services: remote psychological interventions ; Chapter 4. Digital peer support for people with severe mental illness: key concepts and findings overview ; Chapter 5. Web-based psychotherapy and exercise interventions for depressive and anxiety disorders ; Chapter 6. Digital technologies in dementia care -- Section 3. Gamification and serious games in mental healthcare. Chapter 7. Digital games and mental health: a scoping review on gaming disorder in the last decade ; Chapter 8. Gamification applied to autism spectrum disorder ; Chapter 9. Gamification in stroke rehabilitation -- Section 4. Artificial intelligence in mental health. Chapter 10. Artificial intelligence in digital mental health ; Chapter 11. AI chatbots in mental health: are we there yet? -- Section 5. Virtual reality in psychosocial interventions. Chapter 12. Virtual reality and forensic mental health ; Chapter 13. Usability and applications of virtual and augmented reality in older adults ; Chapter 14. Virtual reality environments in pain management -- Section 6. Biosensors. Chapter 15. Biosensors, biofeedback, and neurofeedback. - Mode of access: World Wide Web
Keywords: Mentally ill -- Rehabilitation; Mental health -- Technological innovations